Fully Reversible Metal Deactivation Effects in Gold/Ceria-Zirconia Catalysts: Role of the Redox State of the Support - Cies, Jose M. (2010)
Strong and reversible modification of the chemical properties of supported Au nanoparticles caused by alternating oxidizing (a and c) and reducing (b) pretreatment of Au/CeO2-ZrO2 catalysts were revealed by a methodology that combines FTIR spectroscopy (see picture), studies on the volumetric adsorption of CO and ultimate oxygen storage capacity, determination of metal dispersion by electron microscopy, and X-ray photoelectron spectroscopy.